Factors affecting target INR levels in homebound and ambulatory patients who use warfarin - Tuncer, Ozge; Sakalli, Ayca Asma; Gursoy, Mustafa Ozan (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the rates of reaching target international normalised ratio levels and the factors affecting these rates in patients undergoing warfarin therapy. Method: The prospective cross-sectional study was conducted between 16.08.2023 and 16.11.2023 at Izmir Bozyaka Training and Research Hospital and comprised patients of either gender who had been reciving warfarin therapy for at least 6 months. Those who were under the care of Home Health Services were in group A, while those being followed up at the cardiology outpatient clinic were in group B. All the patients had been receiving regular monitoring for international normalised ratio. Data was collected using a self-designed 41-item questionnaire. Data was analysed using SPSS 27. Results: Of the 200 patients, 100(50%) were in each of the 2 groups. The overall mean age of the sample was 69.54±12.70 years. There were 131(65.5%) females, 108(54%) had international normalised ratiolevel within the target range, 101(50.5%) stated they had received education about warfarin, 120(60%) were aware of the side effects, and 81(40.5%) indicated they experienced complications while using warfarin. Group A patients received more education/information about warfarin, and warfarin-related complications were fewere in such patients (p<0.05). Conclusion: International normalised ratio monitoring among patients under the care of Home Healthcare Service was more reliably and effective compared to cardiology inpatients. Key Words: Warfarin therapy, Anticoagulants, Patients’ education.